Impact loads on the self-elevating unit during jacking operation - Daun, Viktor; Olsson, Fredrik (My University, 2014)
The renewable energy resource of offshore wind is believed to have a great potential in playing an essential role on the future energy market in Europe, but there are complications such as harsh weather and low accessibility. To manage this, most offshore wind turbines of today are installed and maintained using self-elevating units (SEUs). Even though SEUs provide stable platforms easing offshore operations once in an elevated mode, the installation and retrieval phases of the unit itself remain a limiting factor for operation, as impact between the seabed and spudcan may occur due to vessel motion in waves. Limits for these operations are defined by the vessel manufacturer and do generally not account for site-specific parameters, such as soil deformation behaviour and water depth. Neither does the recommended practice for estimating impact loads by classification societies. The objective of this thesis is to develop a method of analysis by which it will be possible to make weather window assessments for the installation and retrieval phases of a SEU. The method of analysis takes site-specific parameters, defined as soil type and water depth, into account in addition to vessel-specific and environmental parameters. The inclusion of site-specific parameters is the novel contribution compared to assessment methodologies used today. A simulation model is developed incorporating a coupled non-linear time-domain analysis of vessel motion and soil-structure interaction. Soil deformation behaviour during impact is described by resistance curves based on a bearing capacity theory, an existing theory initially used for in-situ testing of soils. In addition to the time-domain simulation, an un-coupled FE analysis of structural capacity is made. A structural evaluation criterion against which impact forces are compared is used for weather window assessments. The simulation model is applied on a case study utilizing different soil types to study impact forces and the capacity of the structure for withstanding such impacts and eventually performing a weather window assessment. It has been found that the jacking operation can be divided into two different phases when it comes to loads on the spudcan. A first phase is dominated by vertical forces, which is the focus in this thesis, followed by a phase dominated by horizontal forces. Results from the case study show that including soil deformation behaviour is of paramount importance to the magnitude of the resulting impact forces and that classrecommended practice does indeed produce rather large force estimates. Thus, assessments where site-specific parameters are incorporated could definitely increase the operable weather window for SEUs, and, consequently, increase the economic competitiveness of, for example, the offshore wind industry.
Keywords: Farkostteknik; Vehicle Engineering